414 Screening Developmental Domains In Preterm Children: Diagnostic Validity Of "Parents' Evaluation Of Developmental Status: Developmental Milestones" (PEDS:DM) Assessment Level. (October 2012) - Pritchard, MA; Dassel, T de; Johnston, L; Beller, E; Bogossian, F; Callan, S; Crothers, C; Russo, S; Hovey, D; Cartwright, D
Abstract : Background/aims: Very preterm children (VPT-born < 29 weeks gestation) are at high risk for delay across a range of developmental domains. The diagnostic utility of the Parents' Evaluation of Developmental Status: Developmental Milestones (PEDS:DM) Assessment Level in screening for children with i)domain specific and ii) global cognitive delay was assessed in VPT children. Method: Cross-sectional cohort of infants at 2 and 4-years corrected age for prematurity during 2010. Parents completed the PEDS:DM-Assessment Level in correctly identifying language, motor, self-help and social-emotional domain development which was compared with a blinded 2-year Bayley Scales of Infant Development III, 4-year Wechsler Preschool and Primary Scale of Intelligence-Third Edition and for both ages a Neurosensory Motor Development Assessment and Adaptive Behaviour Assessment System-Second Edition. Diagnostic validity-screening test characteristics were determined for each domain and global cognition. Results: Complete data was available on 149/192 (2-years, N=73 and 4-years, N=76) children. The prevalence for developmental delay using each tools standardized mean ->2 (SD) was lower in all domains and for global-cognition compared to the established cut-off PEDS:DM domain scores (≥25%-16 th percentile). Sensitivity and specificity were consistently high (predominately >70%) as was the negative predictive value (>77%). The positive predictive value was lower reflecting the high over-referral rate. Mothers stated they found the assessment useful in articulating their infants' developmental strengths and weaknesses by domains. Conclusion: This parent friendly tool has good diagnostic utility for identifying domain specific and global cognitive delay and can be used to enhance surveillance, and would be useful in resource restricted environments.